المفارقات في الدلالة غير المرئية للشعر الإلهي "ابن الفارض مثالًا" - الربيعيّ, بان أمين (Tasnim International Journal for Human, Social and Legal Sciences, 2024)
Irony is one of the artistic and stylistic phenomena that excites the recipient and attracts him to the content of the speech. By breaking the recipient’s expectations and causing some surprises by depicting the meeting of contradictions, the meeting of opposites, or the paradox of the poetic image. Sufi poetry, especially the poetry of Ibn al-Farid, was full of types of poetic paradoxes that increase the beauty of this art, and it was represented by various themes, including the paradox of opposites, including The paradoxes represented in rhetorical performance, such as metaphor and metonymy, and the research will look at some examples of these paradoxes by the Sufi poet Ibn Al-Farid to reveal the purpose behind the use of this poetic method.